Bacterial Infection, Airway and Systemic Inflammation and Clinical Outcomes before and after Treatment of AECOPD, a Longitudinal and Cross-sectional Study. (1st February 2015) - Chang, Chun; Zhu, Hong; Shen, Ning; Chen, Yahong; He, Bei; Zhao, Jiangchao; Yao, Wanzhen
Abstract Bacterial infection is a major cause of acute exacerbations of chronic obstructive pulmonary disease (AECOPD), which are associated with significantly increased airway and systemic inflammation. However, the relationship among bacteriology, the resolution of inflammation and clinical outcomes is largely unknown. In this study, we recruited consecutive patients hospitalized for AECOPD with purulent sputum. We measured the airway and systemic inflammation levels, the COPD assessment test (CAT) score and adverse outcomes between patients with and without potentially pathogenic microorganisms (PPM). Among sputum samples collected from the 135 episodes of AECOPD, 42 (31.1%) were PPM-positive at admission. Compared with those in the PPM-negative group, more patients in the PPM-positive group had ≥2 exacerbations in previous year and Anthonisen type I at admission and higher drop in sputum neutrophil, serum hs-CRP and CAT value from exacerbation to the subsequent baseline. No significant differences in the adverse outcomes between the two groups were observed. Among the 38 PPM-positive patients who survived and were discharged from hospital, 19 remained PPM-positive (bacterial persistence group) and 19 PPM-negative (bacterial clearance group). Both inflammation indices and CAT score decreased compared to admission in the two groups, regardless of the bacteriology at discharge. Our data suggest uncultivated bacteria and/or virus might also play important roles in causing inflammation and AECOPD.